PENERAPAN PENDEKATAN SAINTIFIK MELALUI CYCLE LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI SISTEM PENCERNAAN KELAS VIII-B SMP NEGERI 1 IDANOTAE T.P 2022 /2023 - Megawati Telaumbanua (TUNAS : Jurnal Pendidikan Biologi, 2023)
Good learning outcomes are one of the benchmarks to determine the success of a learning process. All of this is caused by the lack of liveliness and curiosity of students during the Biology Science learning process. This study aims to: (1) Describe Biology Science learning on the digestive system material using a scientific approach through the cycle learning learning model, (2) Describe the increase in student learning outcomes on the digestive system material by using a scientific approach through the cycle learning learning model. This type of research is Classroom Action Research (CAR). The instruments used: (a) Student observation sheet, (b) Interview guide sheet, (c) Field notes, (d) Learning achievement test. The research subjects were class VIII-B students of SMP Negeri 1 Idanotae. Based on the results of the study it was found that there was an increase in student activity in the learning process, there was a sense of student responsibility in solving each problem given through worksheets, and students felt happy about learning with a scientific approach through the cycle learning model and there was an increase in student learning outcomes from 80% to cycle I to 90% in cycle II classically. Therefore, a scientific approach through cycle learning can be used as a good learning alternative to improve student learning outcomes on the digestive system material.